Application of high strength steel sheets for motor car bumpers. (5th August 2014) - Shiokawa, M.; Furubayashi, T.; Nousho, H.; Yamazaki, K.; Tanaka, T.; Fukuda, M.
This paper discusses the characteristics of materials used to manufacture impact–resistant parts. Experiments and analyses are described in evaluating material behaviour on the basis of its formability and other requisite properties. The results indicate that impact resistance strength cannot be determined by yield point (YS) and tensile strength (TS) alone, as is normally done. However, it can be correlated to their mean value (YS + TS)/2. It is found that as the mean value increases, the impact resistance strength also increases. From the standpoint of formability, a lower YS value yields more favourable results.